A novel PDE9 inhibitor WYQ‐C36D ameliorates corticosterone‐induced neurotoxicity and depression‐like behaviors by cGMP‐CREB‐related signaling. (2nd May 2018) - Huang, Xian‐Feng; Jiang, Wen‐Tao; Liu, Li; Song, Fang‐Chen; Zhu, Xia; Shi, Gui‐Lan; Ding, Shu‐Ming; Ke, Heng‐Ming; Wang, Wei; O'Donnell, James M.; Zhang, Han‐Ting; Luo, Hai‐Bin; et al.
Summary: Background: Major depressive disorder (MDD) is a mental disease characterized by depressed mood, lifetime anxiety, and deficits of learning and memory. Inhibition of phosphodiesterase 9 (PDE9) has been reported to improve rodent cognitive and memory function. However, the role of PDE9 in MDD, in particular its manifestations of depression and anxiety, has not been investigated. Methods: We examined the protective effects of WYQ‐C36D (C36D), a novel PDE9 inhibitor, against corticosterone‐induced cytotoxicity, pCREB/CREB and BDNF expression by cell viability, and immunoblot assays in HT‐22 cells. The potential effects of C36D at doses of 0.1, 0.5, and 1 mg/kg on stress‐induced depression‐ and anxiety‐like behaviors and memory deficits were also examined in mice. Results: C36D significantly protected HT‐22 cells against corticosterone‐induced cytotoxicity and rescued corticosterone‐induced decreases in cGMP, CREB phosphorylation, and BDNF expression. All these effects were otherwise blocked by the PKG inhibitor Rp‐8‐Br‐PET‐cGMPS (Rp8). In addition, when tested in vivo in stressed mice, C36D produced antidepressant‐like effects on behavior, as shown by decreased immobility time both in the forced swimming and tail suspension tests. C36D also showed anxiolytic‐like and memory‐enhancing effects in the elevated plus‐maze and novel object recognition tests. Conclusion: Our results show that inhibition of PDE9 by C36D produces antidepressant‐ and anxiolytic‐like behavioral effects and memory enhancement by activating cGMP/PKG signaling pathway. PDE9 inhibitors may have the potential as a novel class of drug to treat MDD.